PENGARUH MOTIVASI, PELATIHAN DAN LOYALITAS TERHADAP KINERJA KARYAWAN - Novi Dwi Astuti; Beta Asteria (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
This study aims to determine the effect of motivation, job training and job loyalty factors on employee performance at HS Silver Kotagede employees. The respondents of this study were employees of HS Silver Kotagede. This study uses regression analysis, where this analysis tool is used to determine the extent of the influence of motivation, job training and work loyalty factors on employee performance. The results of this study partially indicate that the motivation variable has a positive and significant effect on employee performance, job training has a positive and significant effect on employee performance, and loyalty has a positive and significant effect on employee performance. The results also show that motivation, training and loyalty simultaneously affect employee performance. The results also prove that the value of R2 (Coefficient of Determination) is 0.586, meaning that the performance variable (Y) can be explained by motivation (X1), training (X2) and compensation (X3) simultaneously at 58.6%.